Pengelolaan Limbah dan Penerapan Akuntansi Lingkungan pada Pabrik Tahu Industri Pink Jaya di Kota Kupang - Muhul, Theresia R.; Celin, Felisia H.; Kolin, Anastasia; Lian, Yohanes Pemandi Lian (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This research analyzes the application of environmental accounting in waste management at the Tofu Pink Jaya Oebufu Industry in Kupang, which has been operating for 25 years. The management of waste from the tofu factory includes handling solid waste, such as tofu dregs, and liquid waste from the production process. Solid waste is sold as animal feed, while liquid waste is partially infiltrated into the ground, directed to control tanks, and utilized for biogas production. The research employs a qualitative method, collecting data through observation, interviews, literature review, and documentation. The findings indicate that while the Pink Jaya tofu factory has not fully implemented environmental cost accounting in its financial reports, it has made technically sound efforts in waste management. The production process incurs main costs, which include raw material costs, labor costs, and overhead costs, all identified as part of environmental costs. This research demonstrates that effective waste management can yield economic benefits while alleviating negative impacts on the environment.